Plasma tumor necrosis factor-α is associated with sarcopenia in elderly individuals residing in agricultural and pastoral areas of Xinjiang, China - Wumaer, Aishanjiang; Maimaitiwusiman, Zhuoya; Xiao, Wenwen; Xuekelati, Saiyare; Liu, Jinling; Musha, Tajiguli; Wang, Hongmei (Frontiers in Medicine, 2022)
Background:Inflammatory reactions play a significant role in the occurrence and development of sarcopenia. Determining the association between specific cytokines and sarcopenia may contribute to revealing the pathophysiological mechanism(s) of the disease and provide valuable information for prevention, diagnosis, and treatment. Previous studies have identified several cytokines associated with sarcopenia; however, to our knowledge, none have involved the population of Xinjiang, China, especially in agricultural and pastoral areas. Accordingly, the present study aimed to investigate the association between sarcopenia and inflammatory cytokines among the elderly natural population in agricultural and pastoral areas of Xinjiang. Methods:From September 2017 to May 2018, using a multi-stage random sampling method, we conducted a cross-sectional epidemiological survey of the community-dwelling older people in Mulei County in Northern Xinjiang and Luopu County in southern Xinjiang.Of the 2,100 participants, the statistical analyses included 1,838 participants with complete data. Comparisons of living habits, disease status, biochemical indexes, and levels of interleukin (IL)-4, IL-6, IL-8, IL-10, and tumor necrosis factor (TNF)-α in sarcopenia and non-sarcopenia participants. Results: In Xinjiang, it revealed no significant differences (i.e., P>0.05) in sex, age, ethnicity, smoking and drinking habits, serum renal function, total cholesterol, and diabetes in elders between the sarcopenia and non-sarcopenia groups. However, triglyceride level (P=0.004), hypertension (P= 0.019), and abdominal obesity (P < 0.001) in the sarcopenia group were significantly higher than those in the non-sarcopenia group. Moreover, the levels of IL-10 (P< 0.001), IL-4 (P≤ 0.001), and TNF-α (P< 0.001) in the sarcopenia group were higher than those in the non-sarcopenia group after adjusting for sex, age, hypertension, blood lipid concentration, and obesity. Furthermore, after adjusting for sex, age, hypertension, obesity, as well as IL-10, IL-4, and IL-6 levels, an increased TNF-α level was found to be a risk factor for sarcopenia. Conclusion:The results of the present study suggest that increased plasma level of TNF-α is significantly associated with sarcopenia among elderly individuals residing in the agricultural and pastoral areas of Xinjiang and reveal that “immune aging” is involved in the pathogenesis of sarcopenia.